Why Translate Science? : Documents from Antiquity to the 16th Century in the Historical West (Bactria to the Atlantic) - Gutas, Dimitri; Burnett, Charles; Vagelpohl, Uwe (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2022)
From antiquity to the 16th century, translation united culturally the peoples in the historical West (from Bactria to the shores of the Atlantic) and fueled the production and circulation of knowledge. The Hellenic scientific and philosophical curriculum was translated from and into, to mention the most prevalent languages, Greek, Syriac, Middle Persian, Arabic, Hebrew, and Latin. To fill a lack in existing scholarship, this volume collects the documents that present the insider evidence provided in contemporary accounts of the motivations and purposes of translation given in the personal statements by the agents in this process, the translators, scholars, and historians of each society. Presented in the original languages with an English translation and introductory essays, these documents offer material for the study of the historical contextualization of the translations, the social history of science and philosophy in their interplay with traditional beliefs, and the cultural policies and ideological underpinnings of these societies. Contributors Michael Angold, Pieter Beullens, Charles Burnett, David Cohen, Gad Freudenthal, Dag Nikolaus Hasse, Anthony Kaldellis, Daniel King, Felix Mundt, Ignacio Sánchez, Isabel Toral, Uwe Vagelpohl, and Mohsen Zakeri.